Regulatory and Disclosure Requirements for Indian IPOs: Grading and Other Issues - Dhanuka, Piyush (2008)
This dissertation examines the effect and usefulness of the various regulations and disclosure policies in the Indian IPO market. The recently introduced Grading System has been used as a tool to analyse the effectiveness of additional mandatory disclosures in the Indian market.